2018
DOI: 10.1088/1361-6404/aaa033
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and analytical approaches to an advection-diffusion problem at small Reynolds number and large Péclet number

Abstract: Obtaining a detailed understanding of the physical interactions between a cell and its environment often requires information about the flow of fluid surrounding the cell. Cells must be able to effectively absorb and discard material in order to survive. Strategies for nutrient acquisition and toxin disposal, which have been evolutionarily selected for their efficacy, should reflect knowledge of the physics underlying this mass transport problem. Motivated by these considerations, in this paper we discuss the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…For example, bacteria may get separated due to advection of fluid flow rather than diffusion. Estimations of Peclet number for motile bacteria at our flow rates (P e = 26310) (20) showed that the bacterial sample flown through the channel length of our device (i.e., 20 mm) would only separate due to advection of fluid flow after the bacteria travels 26,310 times the channel width (1 mm) i.e., approximately 26 meter long. This agreed with our observation that we were not able to collect cells at outlet 2 when we ran both inlets in sodium-free solution (SI Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bacteria may get separated due to advection of fluid flow rather than diffusion. Estimations of Peclet number for motile bacteria at our flow rates (P e = 26310) (20) showed that the bacterial sample flown through the channel length of our device (i.e., 20 mm) would only separate due to advection of fluid flow after the bacteria travels 26,310 times the channel width (1 mm) i.e., approximately 26 meter long. This agreed with our observation that we were not able to collect cells at outlet 2 when we ran both inlets in sodium-free solution (SI Fig.…”
Section: Discussionmentioning
confidence: 99%